Pseudomonas aeruginosa Bloodstream Infection: Importance of Appropriate Initial Antimicrobial Treatment - Micek, Scott T. (American Society for Microbiology, 2005)
Pseudomonas aeruginosa bloodstream infection is a serious infection with significant patient mortality and health-care costs. Nevertheless, the relationship between initial appropriate antimicrobial treatment and clinical outcomes is not well established. This study was a retrospective cohort analysis employing automated patient medical records and the pharmacy database at Barnes-Jewish Hospital. Three hundred five patients with P. aeruginosa bloodstream infection were identified over a 6-year period (January 1997 through December 2002). Sixty-four (21.0%) patients died during hospitalization. Hospital mortality was statistically greater for patients receiving inappropriate initial antimicrobial treatment (n = 75) compared to appropriate initial treatment (n = 230) (30.7% versus 17.8%; P = 0.018). Multiple logistic regression analysis identified inappropriate initial antimicrobial treatment (adjusted odds ratio [AOR], 2.04; 95% confidence interval [CI], 1.42 to 2.92; P = 0.048), respiratory failure (AOR, 5.18; 95% CI, 3.30 to 8.13; P < 0.001), and circulatory shock (AOR, 4.00; 95% CI, 2.71 to 5.91; P < 0.001) as independent determinants of hospital mortality. Appropriate initial antimicrobial treatment was administered statistically more often among patients receiving empirical combination antimicrobial treatment for gram-negative bacteria compared to empirical monotherapy (79.4% versus 65.5%; P = 0.011). Inappropriate initial empirical antimicrobial treatment is associated with greater hospital mortality among patients with P. aeruginosa bloodstream infection. Inappropriate antimicrobial treatment of P. aeruginosa bloodstream infections may be minimized by increased use of combination antimicrobial treatment until susceptibility results become known.